2020
DOI: 10.1002/smll.202000845
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Dysfunction Induced by Chronic Whole‐Body PM2.5 Exposure

Abstract: Fine particulate matter (PM2.5) pollution arouses public health concerns over the world. Increasing epidemiologic evidence suggests that exposure to ambient airborne PM2.5 increases the risk of female infertility. However, relatively few studies have systematically explored the harmful effect of chronic PM2.5 exposure on ovarian function and the underlying mechanisms. In this study, female C57BL/6J mice are exposed to filtered air or urban airborne PM2.5 for 4 months through a whole‐body exposure system. It is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 64 publications
2
33
0
Order By: Relevance
“…The collected mouse ovaries were embedded in paraffin, and serially sectioned (5μm). As previously described [34], the ovary sections were incubated with primary antibody (anti-WIP1 (F-10) (sc-376257, 1:200, Santa Cruz Biotechnology, CA, USA; LC3B Antibody, 1:100, A19665, ABclonal, Wuhan, China; SQSTM1Antibody, 1:100, A11483, ABclonal, Wuhan, China) overnight at 4°C. The next day the ovary sections were incubated with a secondary antibody (HRP-labeled goat Anti-rabbit/mouse IgG (H+L), Servicebio, GB23204, 1:200) for 60 minutes at 37°C.…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 3 more Smart Citations
“…The collected mouse ovaries were embedded in paraffin, and serially sectioned (5μm). As previously described [34], the ovary sections were incubated with primary antibody (anti-WIP1 (F-10) (sc-376257, 1:200, Santa Cruz Biotechnology, CA, USA; LC3B Antibody, 1:100, A19665, ABclonal, Wuhan, China; SQSTM1Antibody, 1:100, A11483, ABclonal, Wuhan, China) overnight at 4°C. The next day the ovary sections were incubated with a secondary antibody (HRP-labeled goat Anti-rabbit/mouse IgG (H+L), Servicebio, GB23204, 1:200) for 60 minutes at 37°C.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…The vaginal smears were tested at 9:00 am. every day for consecutive two weeks as previously described [35].…”
Section: Estrous Cycle Monitoring and Mating Testmentioning
confidence: 99%
See 2 more Smart Citations
“…They reported that the area of the ovary containing primordial follicles was significantly decreased in mice exposed to diesel exhaust prenatally, postnatally or during both developmental periods compared to filtered air controls. Two recent publications have reported on effects of tracheal instillation of PM 2.5 [29] or inhalational exposure [30] to PM 2.5 on ovarian function. Zhou et al [30] reported an increased percentage of irregular estrous cycles and decreased primordial follicle numbers in mice after 4 months of exposure to ambient PM 2.5 compared to controls exposed to filtered air.…”
Section: Introductionmentioning
confidence: 99%